(untitled) (Journal of Global Accounting, 2023)
Forensic accounting roles cannot be overemphasized, especially in the present day corporate atmosphere where fraudulent activities has almost become a common norm, hence the need for insightful exposure of students at the grassroot on how to face this reality. This study evaluates sampled students’ knowledge quality of forensic accounting roles and relevance in fraud detection and prevention, specifically using third and fourth year accounting students of Nnamdi Azikiwe University, Awka totalling 270 students. However, the stratified sampling technique was used in selecting a sample size of 161 students on whom structured questionnaire was administered. The formulated hypotheses were tested using Pearson’s Chi-Squared Statistical Test. The findings revealed that: there is a significant level of student awareness on the use of forensic accounting technique in fraud detection and prevention (p-value = 0.000. It was discovered that forensic accounting courses at the undergraduate level do significantly exposes prospective Investigative Accountants to the requisite skills to detect and prevent fraudulent activities (p-value = 0.000). In conclusion, accounting students at Nnamdi Azikiwe University, Awka, demonstrate a significant level of awareness of forensic accounting practices. The study therefore recommends that by continually improving and updating the curriculum content of forensic accounting courses, academic institutions can better prepare students for possible dynamic challenges that undermine effective detection and combat of fraud professionally in the corporate and public service space of the country